Seroprevalence of chikungunya virus infection among HIV-infected adults in French Caribbean Islands of Martinique and Guadeloupe in 2015: A cross-sectional study. - Elodie Curlier; Laurence Fagour; Cécile Herrmann-Storck; Adrien Staelen; Ingrid Vingadassalom; Sébastien Breurec; Sylvie Abel; Sandrine Pierre-François; Janick Jean-Marie; Cédric Laouénan; Raymond Césaire; Bruno Hoen; et al. (Public Library of Science (PLoS), 2021)
Background In 2014, a first outbreak of chikungunya hit the Caribbean area where chikungunya virus (CHIKV) had never circulated before. Methodology/principal findings We conducted a cross-sectional study to measure the seroprevalence of CHIKV immediately after the end of the 2014 outbreak in HIV-infected people followed up in two clinical cohorts at the University hospitals of Guadeloupe and Martinique. Study patients were identified during the first months of 2015 and randomly selected to match the age and sex distribution of the general population in the two islands. They were invited to complete a survey that explored the symptoms consistent with chikungunya they could have developed during 2014 and to have a blood sample drawn for CHIKV serology. The study population consisted of 377 patients (198 in Martinique and 179 in Guadeloupe, 178 men and 199 women), 182 of whom reported they had developed symptoms consistent with chikungunya. CHIKV serology was positive in 230 patients, which accounted for an overall seroprevalence rate of 61% [95%CI 56-66], with only 153 patients who reported symptoms consistent with chikungunya. Most frequent symptoms included arthralgia (94.1%), fever (73.2%), myalgia (53.6%), headache (45.8%), and skin rash (26.1%). Conclusions/significance This study showed that the seroprevalence of CHIKV infection was 61% after the 2014 outbreak, with one third of asymptomatic infections. Trial registration ClinicalTrials.gov NCT02553369.